Aplicativo multim??dia em plataforma m??vel ???idoso ativo???: proposta de exerc??cio funcional de membros inferiores para idosos - Santos, Cl??udia M??rcia Ventura Teixeira (2016)
In an attempt to adjust the technological advances of today the real growth of the elderly population, in order to contribute to the aspect related to good physical health in the face of changes resulting from the aging process, this study aimed to develop a multimedia application for mobile platform exercises functional with an emphasis on lower limbs in the elderly population. For the realization of this study was carried out a systematic review of the main exercises used for postural control, balance and strength, which were selected by a team of physiotherapists and organized in a practical way, with the heating steps, strengthening, balance and relaxation, as most commonly used for this purpose. A table exercise was related and organized in phases, stages and sequence of exercises to be performed. An old was selected for performing and recording video of the exercises for post application. The application was developed to display screens for easy access, targeting the elderly to navigation, bringing recommendations screens, material to be used and a tutorial that teaches the elderly to use the application. Each year posted shows the embodiment, and the description in audio and written execution. Therefore, the elderly should perform your registration and after the completion of the exercise, mark an effort scale return as answer to the developer. Thus, application development "Active Aging" aims to contribute to the practice of functional exercise, such as maintenance of functional capacity by stimulating active aging.